Conclusion of a probabilistic model to evaluate motorcars recycling and dismantling process in a scarce oil environment - Ferreira, M. A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
The M|G|? queue system, at which customers arrive according to a Poisson process at rate ?, is considered in this study. Using this tool it is built a model to analyse a situation in which motorcars arrive at the system when getting idle, in a scarce conventional energy ambience, and leave it as soon as they are recycled or dismantled. Both situations are modelled with the same purpose. The model allows concluding that when the rhythm of dismantling and recycling of motorcars is greater than the rate at which they become idle, the system has a tendency to get balanced.